Fouling of European freshwater bivalves (Unionidae) by the invasive zebra mussel (Dreissena polymorpha) - Sousa, Ronaldo Gomes (2011)
1. The zebra mussel (Dreissena polymorpha) is well known for its invasive success and its ecological and economic impacts. Of particular concern has been the regional extinction of North American freshwater mussels (Order Unionoida) on whose exposed shells the zebra mussels settle. Surprisingly, relatively little attention has been given to the fouling of European unionoids. 2. We investigated interspecific patterns in fouling at six United Kingdom localities between 1998 and 2008. To quantify the effect on two pan-European unionoids (Anodonta anatina and Unio pictorum), we used two measures of physiological status: tissue mass : shell mass and tissue glycogen content. 3. The proportion of fouled mussels increased between 1998 and 2008, reflecting the recent, rapid increase in zebra mussels in the U.K. Anodonta anatina was consistently more heavily fouled than U. pictorum and had a greater surface area of shell exposed in the water column. 4. Fouled mussels had a lower physiological condition than unfouled mussels. Unlike tissue mass : shell mass ratio, tissue glycogen content was independent of mussel size, making it a particularly useful measure of condition. Unio pictorum showed a stronger decline in glycogen with increasing zebra mussel load, but had a broadly higher condition than A. anatina at the time of study (July). 5. Given the high conservation status and important ecological roles of unionoids, the increased spatial distribution and fouling rates by D. polymorpha in Europe should receive more attention.